Answer:
The solution is x=3 , y=-4 or (3,-4)
Explanation:
Given equations (1 and 2) are:
![3x- 2y = 17\\-2x -5y = 14](https://img.qammunity.org/2021/formulas/mathematics/college/9gne40ybsf2d771xpyd8bqhjlni2xqfq84.png)
To solve a system of equation with elimination method, the co-efficients of one of the variables has to be equated and then the equations are added or subtracted to get an equation in one variable.
Multiplying equation 1 by 2:
![2(3x-2y) = 2*17\\6x-4y = 34\ \ \ \ \ Eqn\ 3](https://img.qammunity.org/2021/formulas/mathematics/college/7bskrepts3xei3p9fh6i9k4vieoozfldg2.png)
Multiplying equation 2 by 3
![3(-2x-5y) = 3*14\\-6x-15y = 42\ \ \ \ Eqn\ 4](https://img.qammunity.org/2021/formulas/mathematics/college/9jgp0uqfi8igp2ffhswq9rq0rvh9l04mqh.png)
Adding equation 3 and 4
![(6x-4y) + (-6x-15y) = 34+42\\6x-4y-6x-15y = 76\\-19y = 76\\(-19y)/(-19) = (76)/(-19)\\y = -4\\](https://img.qammunity.org/2021/formulas/mathematics/college/kcuokb3kpwpjdkrzpgxhwoc921ir1jcjgk.png)
Putting y = -4 in equation 1
![3x-2(-4) = 17\\3x+8 = 17\\3x = 17-8\\3x = 9\\(3x)/(3) = (9)/(3)\\x = 3](https://img.qammunity.org/2021/formulas/mathematics/college/h1kh6q5xt3drddnavrcjwt2buv3m6jcqz2.png)
Hence,
The solution is x=3 , y=-4 or (3,-4)